Analysis of Overall Equipment Effectiveness in Fanuc Line 1 Machines by Minimizing six big losses - Sukanta; Burhan N.; Setiawan; Dessy Agustina Sari (Journal of Sustainable Engineering: Proceedings Series, 2019)
The company produces several automotive components in Karawang. For the production process using Fanuc machines on Line1, but the results of evaluating the performance of the engine Fanuc Line1 engine effectiveness is not optimal. It was alleged that due to the planning and maintenance of the management machinery was not good, so that the frequency of damage to the machine was still high, which gave the effect that the production was not achieved. For this reason, the effectiveness of the use of Fanuc line1 is done by using the Overall Equipment Effectiveness (OEE) method with the Six big losses calculation approach so that the level of efficiency can be known. The results showed that the magnitude of the OEE value on Fanuc line1 machines in April – August 2018 amounted to 78.82%, this value is still below the JIPM standard of 85%. The amount of Losses is influenced by reduced speed loss of 57.47% and breakdown loss of 22.79%.